CORRELATIVE ASPECTS OF LANGUAGE SPECIFIC OPERATION AND ARITHMETIC PROCESSING IN BILINGUALS’ BRAIN; AN OVERVIEW OF BEHAVIOURAL AND NEUROLOGICAL STUDIES - Erlyna Abidasari (Englisia: Journal of Language, Education, and Humanities, 2014)
This study talks about what aspects correlated between the language specific operation and arithmetic processing skills that occur in bilingual people’s brains. Some studies toward the behaviour and neurology’s aspects are discussed as well as their findings in order to answer the research questions of the study. The discussions reveal that both skills have a positive correlation and that both occur in the brain’s left hemisphere; however, the left hemisphere largely participates in automatic language specific operations and simple calculations, while the right hemisphere dominates advanced control processing operations in calculation (e.g. calculus, logarithm) and language information transfer. In addition, studies show that the bilinguals’ language dominance does not clearly determine the correlation between the language and arithmetic skills. Further, in order to retain better arithmetic concepts, comprehensive and simultaneous training should be conducted in both languages and in the early stage of language development, especially during bilinguals’ critical age of language learning.